Characteristics Associated with First Aid and Cardiopulmonary Resuscitation Training and Use in Queensland, Australia. Issue 2 (10th April 2019) - Franklin, Richard C.; Watt, Kerrianne; Aitken, Peter; Brown, Lawrence H.; Leggat, Peter A.
Abstract : Introduction: First aid, particularly bystander cardiopulmonary resuscitation (CPR), is an important element in the chain of survival. However, little is known about what influences populations to undertake first aid/CPR training, update their training, and use of the training. Objectives: The aim of this study was to explore the characteristics of people who have first aid/CPR training, those who have updated their training, and use of these skills. Methods: As part of the 2011 state-wide, computer-assisted telephone interviewing (CATI) survey of people over 18 years of age living in Queensland, Australia, stratified by gender and age group, three questions about first aid training, re-training, and skill uses were explored. Results: Of the 1, 277 respondents, 73.2% reported having undertaken some first aid/CPR training and 39.5% of those respondents had used their first aid/CPR skills. The majority of respondents (56.7%) had not updated their first aid/CPR skills in the past three years, and an additional 2.5% had never updated their skills. People who did not progress beyond year 10 in school and those in lower income groups were less likely to have undertaken first aid/CPR training. Males and people in lower income groups were less likely to have recently updated their first aid/CPR training. People with chronic health problems were in a unique demographic sub-group; they were less likely to have undertaken first aid/CPR training but more likely to have administered first aid/CPR. Conclusion: Training initiatives that target people on the basis of education level, income group, and the existence of chronic health problems might be one strategy for improving bystander CPR rates when cardiac arrest occurs in the home. Franklin RC, Watt K, Aitken P, Brown LH, Leggat PA. Characteristics associated with first aid and cardiopulmonary resuscitation training and use in Queensland, Australia. Prehosp Disaster Med . 2019;34(2):155–160